Complicity in fin-de-siècle literature - Craske, H (2021)
This thesis analyses the representation and creation of complicity in fin-de-siècle French literary culture, exploring how particular genres – from murder fiction to saucy magazines – encouraged the creation of collusive relationships between writers, readers, and critics. After considering relevant legal definitions and contexts in the introduction, chapter 1 discusses writers’ moral complicity and literary ‘bad influence’ in Paul Bourget’s Essais de psychologie contemporaine (1883), Un crime d’amour (1886), and Le Disciple (1889). Analysing these texts alongside their reception, I suggest that literary guilt was less a discernible category than a product of external interactions. Chapter 2 considers the imbrication between popular, scientific, and literary representations of crime, highlighting how murder became a source of ironic appropriation in fin-de-siècle literature. The chapter focuses on Rachilde’s Nono (1885) and Émile Zola’s La Bête humaine (1890): narratives whose haunting sense of guilt incriminates both characters and readers, while implicating judicial and moral discourses in unjust judgements. Chapter 3 analyses a polemical media exchange in a little magazine called Le Zig-Zag, and two romans à clefs about Jean Lorrain and Rachilde, written by their mutual friend Oscar Méténier. I examine how this group of avant-garde writers re-appropriated scandal as part of an alternative collective aesthetic and created a sense of collusion by inviting readers ‘in the know’ to unravel half-veiled secrets about their non-normative gender and sexual identities. The final chapter analyses Don Juan, an exemplary ‘revue légère’ (or ‘saucy magazine’) published at the turn of the century (1895–1900). I show that by wielding sex appeal, shared humour, and textual structures appealing for response and involvement, Don Juan created forms of erotic complicity between text, collaborator, and reader.